Assessing Lithuania’s Competitiveness in the Context of EU Enlargement - Karpavičius, Henrikas (Ekonomika, 2007)
After Lithuania’s accession to the EU, the participation of Lithuanian enterprises in a very sizeable intra-EU trade, unrestricted by protectionist measures, acquires an ever greater importance. In 2005, Lithuania’s exports to the EU amounted to 65% of total exports, whereas imports reached 60%. These figures would seem at first sight to reflect positively on Lithuania’s competitiveness in the EU and confirm the assertions of many prominent economists about the multi-faceted benefits of foreign trade to its preachers. To gain a deeper understanding of Lithuania’s comparative advantage, a detailed analysis by product groups has been conducted, using the metrics of Revealed Comparative Advantage (RCA) and Relative Trade Balance (RTB). Quantifying comparative advantage is particularly important to small and rapidly growing economies that are still looking to define their both short- and long-term economic development priorities. The developments of intra-EU trade are affected by a multitude of factors, however, we single out the effects of opening of the EU market to imports from new ‘economic centres’, especially China, because of the competitive threat it poses to countries like Lithuania. In this context, our analysis using RCA and RTB metrics highlights unfavourable, both direct and indirect, tendencies for Lithuania. Looking at Sino-Lithuanian trade in goods that account for the lion’s share of Lithuania’s total exports (textile, machines and mechanical equipment, electrical equipment, transport vehicles and equipment, and furniture), it becomes clear that the trade balance in these goods is shifting not in Lithuania’s favour. Furthermore, a breath-taking growth in the Sino-EU trade and, in particular, EU’s deteriorating trade balance with China in the aforementioned goods categories over the 2003-2005 period raises serious questions about the future of Lithuania’s export industries. The structural analysis of Lithuania’s foreign trade using the BEC (Broad Economic Categories) classification reveals a slightly positive RTB value in the ‘consumption goods’ category, but a substantially negative value in the ‘intermediate’ and ‘investment goods’ categories. This seems to confirm the conclusions reached in a study by European Commission in 2005, that the new member states (including Lithuania), owing to their exports of low to medium grade goods by technological sophistication, will be severely pressurised by competition from China and other fast-developing countries. Analysis of foreign direct investment (FDl) flows by economic sectors does not provide evidence that major changes in the export structure are underway to mitigate the effects of competition with China and other fast-growing countries.